Accuracy and effectiveness of HPV mRNA testing in cervical cancer screening: a systematic review and meta-analysis. Issue 7 (July 2022) - Arbyn, Marc; Simon, Marie; de Sanjosé, Silvia; Clarke, Megan A; Poljak, Mario; Rezhake, Remila; Berkhof, Johannes; Nyaga, Victoria; Gultekin, Murat; Canfell, Karen; Wentzensen, Nicolas
Summary: Background: Cervical cancer screening tests that identify DNA of the main causal agent, high-risk human papillomavirus (HPV) types, are more protective than cervical cytology. We systematically reviewed the literature to assess whether tests targeting high-risk HPV (hrHPV) mRNA are as accurate and effective as HPV DNA-based screening tests. Methods: We did a systematic review to assess the cross-sectional clinical accuracy to detect cervical intraepithelial neoplasia of grade 2 or worse (CIN2+) or 3 or worse (CIN3+) of hrHPV mRNA versus DNA testing in primary cervical cancer screening; the longitudinal clinical performance of cervical cancer screening using hrHPV mRNA versus DNA assays; and the clinical accuracy of hrHPV mRNA testing on self-collected versus clinician-collected samples. We identified relevant studies published before Aug 1, 2021, through a search of Medline (PubMed), Embase, and CENTRAL. Eligible studies had to contain comparative data addressing one of our three clinical questions. Aggregated data were extracted from selected reports or requested from study authors if necessary. QUADAS and ROBINS-1 tools were used to assess the quality of diagnostic test accuracy studies and cohort studies. To assess cross-sectional clinical accuracy of mRNA testing versus DNA testing and clinical accuracy of hrHPV mRNA testing on self-collected versus clinician collected samples, we applied meta-analytical methods for comparison of diagnostic tests. To assess the longitudinal clinical performance of cervical cancer screening using hrHPV mRNA versus DNA assays, we compared the longitudinal sensitivity of mRNA tests and validated DNA tests for CIN3+ and the relative detection of CIN3+ among women who screened negative for hrHPV mRNA or DNA (both used as measures of safety) at baseline and pooled estimates by years of follow-up. A random-effect model for pooling ratios of proportions or risks was used to summarise longitudinal performance. Findings: For the hrHPV mRNA testing with APTIMA HPV Test (APTIMA), the cross-sectional accuracy could be compared with DNA assays on clinician-collected samples in eight studies; longitudinal performance was compared in four studies; and accuracy on self-samples was assessed in five studies. Few reports were retrieved for other mRNA assays, precluding their evaluation in meta-analyses. Compared with validated DNA assays, APTIMA was similarly sensitive (relative sensitivity 0·98 [95% CI 0·95–1·01]) and slightly more specific (1·03 [1·02–1·04]) for CIN2+. The relative sensitivity for CIN3+ was 0·98 (95% CI 0·95–1·01). The longitudinal relative sensitivity for CIN3+ of APTIMA compared with DNA assays assessed over 4–7 years ranged at the study level from 0·91 to 1·05 and in the pooled analysis between 0·95 and 0·98, depending on timepoint, with CIs including or close to unity. The detection rate ratios between 4 and 10 years after baseline negative mRNA versus negative DNA screening were imprecise and heterogeneous among studies, but summary ratios did not differ from unity. In self-collected samples, APTIMA was less sensitive for CIN2+ (relative cross-sectional sensitivity 0·84 [0·74–0·96]) but similarly specific (relative specificity 0·96 [0·91–1·01]) compared with clinician-collected samples. Interpretation: HrHPV RNA testing with APTIMA had similar cross-sectional sensitivity for CIN2+ and CIN3+ and slightly higher specificity than DNA tests. Four studies with 4–7 years of follow-up showed heterogeneous safety outcomes. One study with up to 10 years of follow-up showed no differences in cumulative detection of CIN3+ after negative mRNA versus DNA screening. APTIMA could be accepted for primary cervical cancer screening on clinician-collected cervical samples at intervals of around 5 years. APTIMA is less sensitive on self-collected samples than clinician-collected samples. Funding: Horizon 2020 Framework Programme for Research and Innovation of the European Commission, through the RISCC Network, WHO, Haute Autorité de la Santé, European Society of Gynaecological Oncology, and the National Institute of Public Health and the Environment.